Clinical Use of Ultrasound in Obstetrics - Saba Kamal Mahmood (Journal of Global Pharma Technology, 2019)
During the past three years, ultrasound diagnostic procedures have been important and useful means in clinical practice of obstetrics and gynecology. Ultrasound images of the flow, whether color flow or spectral Doppler, are obtained from motion measurements. In ultrasound scanners, a series of pulses are transmitted to detect blood movement. Echoes of fixed tissues are the same from pulse to pulse. The echoes of the transition from scatter to slight differences appear at the time of signal return to the receiver. These differences can be measured as a direct time difference, or usually, in terms of the phase shift from which the Doppler frequency is obtained. It is then processed to produce either a color flow display or Doppler ultrasonography.